A Review of Phage Therapy for Aquaculture Applications: Efficacy, Health Ramifications and Research Challenges - Louise James; Tamsyn M. Uren Webster; Gethin Thomas; Mathias Middelboe; Sofia Consuegra (Fish and Fisheries, 2026)
The emergence of antimicrobial resistance has encouraged a reappraisal of bacteriophage therapy for the mitigation of bacterial diseases in different environmental settings, including aquaculture. Here, we review aquaculture applications of phage therapy by considering its efficacy and potential for broader host‐associated effects, including host immunity, microbiome composition and behaviour. The advantages of phage therapy for aquaculture include the natural abundance and diversity of phages in water, and their self‐propagation, host specificity, low environmental impact and diverse administration routes. Although the efficacy of phage therapy in controlling the prevalence of bacterial pathogens across various aquaculture species is well demonstrated, the diversity of phage administration methods, experimental conditions, target strains and host physiologies have prevented a clear consensus being reached regarding the suitability of phage therapy for aquaculture. The application of phage therapy as an antimicrobial strategy induces gentler immune modulation compared to antibiotics and disinfectants, which often induce dysbiosis in host microbiomes by eliminating beneficial or commensal bacteria. However, there are divergent results regarding the influence of phage administration upon host microbiome composition and dynamics, with potentially important health implications that require further research. How phage immunogenicity may influence the host immune response is also unclear. Additional concerns include phage‐neutralising antibody production, phage‐resistant bacteria and horizontal gene transfer of antimicrobial resistance. Together, these represent areas warranting further research in aquaculture, along with the development of suitable fish models that demonstrate the broad applicability of phage therapy across multiple species.